IMPACT OF DIGITAL TECHNOLOGIES ON PEOPLE HEALTH AND MEANS TO AVOID INFORMATION FATIGUE - Miseviciene, Regina; Rimavicius, Vidmantas; Makackas, Dalius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Internet become as basic component of daily routine. Although the Internet has many positive aspects, most people spend too much time on their smart devices spending less time playing outdoors. A decrease in physical activity not only sets up information fatigue, which leads to increase in diseases of the nervous and heart systems. Many of scientific articles deal only with the features of information fatigue and its consequences for human health, however research articles that analyze tools that can protect against information fatigue have not been found. Only commercial companies advertise their software, which help monitor what users are doing on their computer. Novelty of the article is that it explores how information technology affects young people lives and analyses software that can help control working time with these smart devices also.